2021
DOI: 10.3892/etm.2021.10415
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of spontaneous bacterial peritonitis in Romanian adults with liver cirrhosis: Focus on the neutrophil‑to‑lymphocyte ratio

Abstract: Spontaneous bacterial peritonitis (SBP) is a severe complication of liver cirrhosis whose diagnosis is based on a polymorphonuclear leukocyte (PMN) value >250 mm 3 , yet this PMN value cannot identify all existing types. The aim of our study was to determine the clinical and biological factors that were associated with SBP and predict its occurrence, focusing on the neutrophil-to-lymphocyte ratio (NLR) as one of them. Our retrospective study included 216 patients with liver cirrhosis who were hospitalized betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…Of 14 studies, six studies were on infection with 2786 hospitalized cirrhotic patients, of whom 934 developed infection [ 18 , 20 22 , 24 , 26 ]. Others were on SBP with 1573 cirrhotic patients with ascites, of whom 557 developed SBP [ 14 – 17 , 19 , 23 , 25 , 27 ]. The process of inclusion and exclusion is detailed in the PRISMA flow diagram, which is provided in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 14 studies, six studies were on infection with 2786 hospitalized cirrhotic patients, of whom 934 developed infection [ 18 , 20 22 , 24 , 26 ]. Others were on SBP with 1573 cirrhotic patients with ascites, of whom 557 developed SBP [ 14 – 17 , 19 , 23 , 25 , 27 ]. The process of inclusion and exclusion is detailed in the PRISMA flow diagram, which is provided in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All of them were written in English. Seven studies reported the results of receiver operating characteristic (ROC) curve analysis, including the best cutoff point, sensitivity, and specificity of NLR in the prediction of SBP [ 14 – 17 , 19 , 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations